Gesture in speaking tasks beyond the classroom: An exploration of the multimodal negotiation of meaning via Skype videoconferencing on mobile devices - Lee, Helen; Hampel, Regine; Kukulska-Hulme, Agnes (System (Linköping), 2019)
This qualitative study attempts to explicate the role of gestures formed with learners’ hands and technology during second language speaking tasks via Skype videoconferencing tools, accessed on mobile devices. The theory of negotiation of meaning according to the Varonis and Gass model of non-understandings (1985) underpins the study. Data was collected from ten intermediate English language learners via recordings of their task-based interactions and stimulated recall interviews. The study found that gestures support forms of negotiation through affording participants a range of visual and embodied clues which operate in close conjunction with their language use. Findings suggest that gestures play a role in the establishment of joint attention and negotiation of vocabulary; and they are exploited to appeal for assistance and scaffold interlocutors. In some instances, gestures also potentially confuse learners. The deployment of mobile technologies was found to transform and mediate gestures in complex ways. Learners also experience challenges in their co-ordination of multimodal talk from beyond the classroom.